2018
DOI: 10.1177/0016986218800068
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Case Study of Exceptional Leadership Talent

Abstract: The development of leadership talent in a gifted individual was the focus of this 15-year longitudinal case study. Four major themes explained the development of his leadership talent. Crucial family factors and support served as a foundation for his psychosocial development and contributed significantly to his talents as a leader. Emotional intelligence evident in childhood, adolescence, and adulthood was an important asset as his leadership skills grew. In addition, strong practical intelligence applied to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 18 publications
0
14
1
Order By: Relevance
“…The role of opportunity was notably absent in the definitions of leadership, but it was a recurring theme in author recommendations. For the individual in Hébert’s (2019) longitudinal single case study, L. J.’s leadership ability emerged early, was systematically strengthened in adolescence and emerging adulthood, and was applied and adapted throughout his graduate education, early career, and later career specialization. L. J.’s talent for learning languages, his leadership skills, and his openness to new experiences gave him the opportunity to serve in the United States Navy as a Naval Special Warfare officer (Hébert, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The role of opportunity was notably absent in the definitions of leadership, but it was a recurring theme in author recommendations. For the individual in Hébert’s (2019) longitudinal single case study, L. J.’s leadership ability emerged early, was systematically strengthened in adolescence and emerging adulthood, and was applied and adapted throughout his graduate education, early career, and later career specialization. L. J.’s talent for learning languages, his leadership skills, and his openness to new experiences gave him the opportunity to serve in the United States Navy as a Naval Special Warfare officer (Hébert, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…For the individual in Hébert’s (2019) longitudinal single case study, L. J.’s leadership ability emerged early, was systematically strengthened in adolescence and emerging adulthood, and was applied and adapted throughout his graduate education, early career, and later career specialization. L. J.’s talent for learning languages, his leadership skills, and his openness to new experiences gave him the opportunity to serve in the United States Navy as a Naval Special Warfare officer (Hébert, 2019). Academic ability did explain some of the variance in teacher ratings of leadership ability for students enrolled in a high school leadership course, but interactions between ability and nonacademic variables, such as motivation, also explained a notable amount of variance (Schneider et al, 1999).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For students with HA, family relationships are critical, as parents are the first to identify characteristics associated with this condition in their sons and daughters, recognising them and therefore providing environments that enrich and enhance their superior cognitive characteristics (GOMEZ-ARIZAGA; TRUFFELLO; KRAUS, 2019; IVIE; CZUJKO; STOWE, 2002). Likewise, it has been observed that for students with HA, the parental figure of the same sex can constitute a role model, in terms of both cognitive and socio-affective characteristics (HÉBERT, 2018). Similarly, fathers also tend to encourage early interests in both their daughters and sons, based on the observation of their superior cognitive characteristics or signs of precocity (COLEMAN, 2016;KINGSBURY;HEYLIGHEN, 2019).…”
Section: Parents As Influential Figures In the Development Of Interestsmentioning
confidence: 99%